2016
DOI: 10.1155/2016/8985690
|View full text |Cite
|
Sign up to set email alerts
|

Studying Maximum Plantar Stress per Insole Design Using Foot CT-Scan Images of Hyperelastic Soft Tissues

Abstract: The insole shape and the resulting plantar stress distribution have a pivotal impact on overall health. In this paper, by Finite Element Method, maximum stress value and stress distribution of plantar were studied for different insoles designs, which are the flat surface and the custom-molded (conformal) surface. Moreover, insole thickness, heel's height, and different materials were used to minimize the maximum stress and achieve the most uniform stress distribution. The foot shape and its details used in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
0
16
1
Order By: Relevance
“…Previous study showed that the custom-molded insole reduced maximum stress 40% more than the flat surface insole. In the increase of insole thickness, stress distribution becomes more uniform and maximum stress value decreases up to 10% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that the custom-molded insole reduced maximum stress 40% more than the flat surface insole. In the increase of insole thickness, stress distribution becomes more uniform and maximum stress value decreases up to 10% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that the custom-molded insole could reduce stress compared with the flat insole. The thickness, heel's height, and materials of proper insole could minimize the peak plantar stress and achieve uniform stress distribution [ 6 ]. The material and arch height of insole in the sport shoes have a significant effect on biomechanical characteristics of the foot [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…al (2012) in their FEM analysis of insoles. The peak stress of 1.17 MPa is significantly higher than the values quoted by Cheung & Zhang (2006) and Sarikhani et al (2016) who calculated maximum stresses of just 156 kPa and 100 kPa respectively for similar analyses (see section 2.1.1 for further details). However, the simulation conducted by this study examined a worst-case scenario of a 90 kg person running, compared to the 70 kg static cases from the earlier studies.…”
Section: Calculation Of Forces On Orthoticcontrasting
confidence: 52%
“…Cheung & Zhang (2006) found that a 70 kg person in a standing position generates a peak stress of around 156 kPa in the forefoot and heel regions. By comparison a similar study also using a 70 kg stationary load case produced peak stresses of just 100 kPa (Sarikhani, et al, 2016). As such the literature is unable to set out a definitive loading case which the orthotics should withstand.…”
Section: Design Considerationsmentioning
confidence: 95%
“…26 Interestingly, the authors also verified that the increase in thickness above 1 cm was ineffective at improving plantar pressure distribution, emphasizing that insoles thicknesses between 0.5 and 0.75 cm would be more favorable for patients with plantar fasciopathy. 26…”
Section: Discussionmentioning
confidence: 88%